The Effect of Financial Literacy, Income, Risk Tolerance on Investment Decisions with Investment Interest as a Mediating Variable - Paramitha, Made Ayu Siwi; Gorda, Anak Agung Ngurah Oka Suryadinatha (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to identify the effect of financial literacy, income, risk tolerance, investment interest with investment decisions. In addition, the study also identifies investment interest as a mediating variable on financial literacy, income, and risk tolerance. The population in this study were investors located in Denpasar City. The sample was selected by purposive sampling method. Data was collected using a questionnaire. Model testing is done with inferential statistical analysis techniques and hypothesis testing is done with the t-statistic test. The results of testing the direct effect between variables obtained a positive and significant value with p <0.05. The results also obtained the effect of financial literacy, income, and risk tolerance on investment decisions providing an R-square value of 0.778, while the effect of financial literacy, income, risk tolerance and investment interest on investment decisions provided an R-square value of 0.747. The study found that the better financial literacy, income, risk tolerance, and investment interest will increase the investment decisions of investors. The government is expected to provide space for people to learn about investment so as to increase potential and quality investors in Indonesia.